Nanocarnation-like Nickel Oxide Thin Film: Structural and Optical Properties - Parimon, N.; H. Mamat, M.; A. R. Abdullah, M.; S. Ismail, A.; R. W. Ahmad, W.; B. Shameem Banu, I.; Rusop, M. (International Journal of Engineering and Technology, 2018)
Herein, the structural and optical properties of highly porous nanocarnation-like nickel oxide (NiO) thin film in possibility of sensing applications were reported. The highly porous nanocarnation-like NiO was grown on indium tin oxide (ITO) glass substrates by using sonicated sol-gel immersion process. The grown film was characterized in details to examine the structural and optical properties using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Raman spectroscopy, and ultraviolet–visible–near infrared (UV-vis-NIR) spectroscopy, respectively. The XRD pattern reveals that the grown nanocarnation-like NiO film has crystalline NiO with a cubic structure. The UV-vis-NIR spectrum demonstrates that the average transmittance value of the sample in the visible region is approximately 48 % transmission. The results showed that, in view of highly porous nanocarnation-like NiO structure exhibited a great influence on its possibility for sensing applications.